Modeling Bandung Traffic Jam Using Simulation Of Urban Mobility - Yapinus, Pin Panji; P., Ary Setiajadi (Zenit, 2015)
The population density in Bandung City is rapidly increasing. It is also followed by the increasing number of vehicles. Today, people are able to get new vehicles much easier than everbefore. The public services such as trains, buses, and "angkots" (public transportation) are still uncomfortable to most people for many reasons. On the other side, the streets in Bandung City cannot withstand the increasing density of the vehicles. The purpose of making this simulation by means of this research is to make a measurement tool that can be used to determine the solution to the traffic congestion issue in Bandung City. Making the simulation is done by editing the file osm fromwww.openstreetmap.org, converting, and adjusting traffic lights and vehicles at random into the simulation. By entering the total car-type vehicles at random, the simulation illustrates a significantly high congestion.Kata kunci: capacity, streets of Bandung City, vehicles